Perceived Cognitive Deficits, Emotional Distress and Disability following Whiplash Injury - Michael JL Sullivan; Erin Hall; Rosita Bartolacci; Maureen E Sullivan; Heather Adams (Pain Research and Management)
OBJECTIVES: To describe the pattern of perceived cognitive deficits in patients with whiplash injury, to examine the relation between perceived cognitive deficits and disability, and to examine the determinants of perceived cognitive deficits in patients with whiplash injury.